Application of Sketch Learning: Media 3 Dimensi Berupa Alat Peraga untuk Meningkatkan Minat Belajar Siswa pada Proses Pembelajaran - Muhammad Kholil; Rizki Fitriya Nitasari (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research discusses the use of 3-dimensional teaching aids in the context of learning butterfly metamorphosis for grade 2 students at the MI Institute. Ihyaul Islam. The aim of the research is to determine the application of 3-dimensional sketch learning media in the form of teaching aids to increase student interest in learning. Through qualitative methods with a case study approach, data was obtained from observations, conducting interviews with school principals, teachers and students, as well as documentation of the learning process. The research results show that the use of 3-dimensional teaching aids significantly increases students' interest in learning. This media facilitates a better understanding of the concept of butterfly metamorphosis, improves students' memory, and stimulates active involvement in learning. Thus, the use of 3-dimensional teaching aids is considered important in creating an interesting, interactive and effective learning atmosphere for students in understanding science material. These findings have positive implications for the quality of learning, encouraging students' interest in learning, stimulating active involvement in the educational process, and making the learning atmosphere in the classroom more enjoyable and less boring.